Fibre-reinforced concrete as an aspect of green construction technology - Radmila Sinđić Grebović; Marko Grebović (Advances in Civil and Architectural Engineering)
This study investigates the effects of the different types and percentages of fibre reinforcements in concrete on structures' design life to advance the phase of the products' use. Clearly, relatively wide cracks in the concrete during the structure's exploitation, using fibre reinforcement, will be transformed into a pattern of fine microcracks. Restricting the width of cracks using fibres in concrete advances the structure's design life, increasing its durability. Moreover, the investigation of the correlation between compressive and tensile strength indicates a significant increase in the tensile strength of fibre-reinforced concrete. The safety factor against failure of fibre-reinforced beams on the shear strength for mixtures with different amounts of fibres increased approximately two times with the growth of content steel fibre from 0,25 to 1,50 %. Concrete with recycled coarse aggregates and fibre reinforcement shows similar strength and ductility properties as concrete with natural aggregates. Using the synergy of positive effects of increased recycled coarse aggregate content, reduced participation of cementitious materials, and improved tensile behaviour by incorporating fibres in the concrete mixture is believed to be an option for green concrete with improved resistance to aggressive environmental influences. Cost-effective and environmentally friendly methods to advance fibre-reinforced concrete sustainability imply increasing the recycled aggregate content and lowering the consumption of cementitious materials with improved behaviour in exploitation.